If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 4v = -4 Solving 8 + 4v = -4 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 4v = -4 + -8 Combine like terms: 8 + -8 = 0 0 + 4v = -4 + -8 4v = -4 + -8 Combine like terms: -4 + -8 = -12 4v = -12 Divide each side by '4'. v = -3 Simplifying v = -3
| 4a+6-3a-2= | | S/-3=2 | | h=2*3.14*r^2+2*3.14*r*16.2 | | 25n-40=-62 | | 3/4(8y-12)= | | .75t=50 | | F(x)=12x-6 | | 8(-5+4)= | | .75t=.50 | | (2y+9)(2y+9)=81 | | (4-2j)/(2-1j) | | 5.26s-2.01=-8.94 | | -2g+7= | | -9s+18-18=18s-4-2 | | 7v+224=-84v | | 3v+9+v=2v-2+3 | | -38-37= | | 10+5x-x=10+4x+4 | | 45=26+b | | X+2+x-10=90 | | 2v+1=-3v+8v+10 | | 6u-12+2=6u-10 | | 14m-2m-2m-8m=12 | | 45=26 | | h=2*3.14*30.25+2*3.14*5.5*18.7 | | 3y+6-y=2y-2+10 | | 729/1.000 | | 6x+12=3x-9 | | 14g-13g=17 | | -2x-4+7=3x+18 | | 4x-2(x-2)=-5+4x-3 | | 3w+6+w=4w-4+10 |